Cerebrovascular Events After Stentless Aortic Valve Replacement During a 9-Year Follow-Up Period - Gulbins, H.; Florath, Ines; Ennker, J. (2008)
Background: One major advantage of biologic aortic valve prostheses is their low thrombogenicity compared with mechanical prostheses. The purpose of this study was to evaluate the incidence of cerebrovascular events during long-term follow-up after stentless aortic valve replacement. Methods: Between 1996 and 2005, 1,014 patients (mean age, 73 years; range, 20 to 90 years) received stentless aortic valve replacement (Freestyle; Medtronic, Minneapolis, MN) and were included into the systematic follow-up that was closed in 2006 with a completeness of 94.7% and a mean follow-up interval of 3 years (range, 0.5 to 9.8 years). Predictors for freedom from cerebrovascular events were identified by Cox regression. Results: Overall survival was 53% ± 5% after 8 years (mean, 6.8 ± 0.2 years). Permanent atrial fibrillation at time of surgery was a strong predictor of impaired survival during follow-up. Freedom from cerebrovascular events during follow-up was 68% ± 5% at 9 years of follow-up. Multivariate regression analysis revealed previous stroke, age at implant, diabetes mellitus, and carotid lesions as significant risk factors. Especially age older than 75 years was a strong risk factor for cerebrovascular events during follow-up (p = 0.004). Atrial fibrillation was not an independent risk factor for cerebrovascular events (p = 0.26) but was a strong predictor of poor survival (p < 0.001) during follow-up. There was no influence of technique of implantation (subcoronary versus full root; p = 0.41), sex (p = 0.35), additional bypass grafting (p = 0.65), and the size of the implanted prosthesis (p = 0.47). Conclusions: The risk of cerebrovascular events during follow-up after stentless aortic valve replacement is related to the individual risk factors of the patients rather than to the valve prosthesis itself. Without additional risk factors, patients with these aortic valve prostheses showed an incidence of cerebrovascular events similar to those reported for a healthy population adjusted for age. © 2008 The Society of Thoracic Surgeons.